Caffeine intake enhances endurance performance in sub-elite but not in elite athletes - Smolka, O.; Kumstat, M. (Annales Kinesiologiae, 2014)
The aim of our contribution is to evaluate the influence of caffeine (CAF) ingestion on maximal power output (MPO) during endurance performance. Two groups of men - 10 sub-elite cyclists and 8 elite cyclists completed a randomized, crossover, double-blind study. Over the course of three days participants completed three identical experimental tests (60min cycling time trial on 70 % VO2max followed by test to exhaustion). Three experimental meals - a combination of 500ml water, a gel supplement and a specific dose of CAF: a placebo (PLA, no caffeine), CAF2 (2 mg / kg body weight (BW)) and CAF7 (7 mg / kg BW) were administered 45min prior to the start of the experimental tests. Subjective RPE values were determined using the Borg 20-category scale. The results show significant differences between MPOPLA and MPOCAF7 and between MPOCAF2 and MPOCAF7 with p = 0.018 and p = 0.019, respectively, in the sub-elite cyclists group only. The mean MPO during experimental test in sub-elite cyclists, but not in elite cyclists, was significantly enhanced following caffeine ingestion (p = 0.05). These findings indicate that caffeine intake at recommended levels is not associated with improved performance in a professional level cyclist. The results of the comparison of the experimental situations using the Borg scale are not persuasive. We found a significant difference(0.008356) between the PLA and CAF2 experimental measurements (p < 0.05). The level of substantive significance was assessed using Cohen`s coefficient effect and only a small "size of effect" (0.19) was found. It is therefore not possible to determine whether the Borg scale might be used to define the effects of caffeine ingestion on endurance performance, due to the multifactorial effects of caffeine.